PENGARUH TEKNIK MASSASE EFFLEURAGE TERHADAP TINGKAT NYERI PADA IBU BERSALIN - Eline Charla Sabatina Bingan (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
A mother who faces childbirth tends to be afraid especially with primigravida. Because thatpain must be alleviated effectively because pain accompanied by stress reactions haveharmful effects on the mother and fetus. One way to overcome the problem of pain duringlabor is a Massase Effleurage. Abdominal massage or massage (Effleurage) is a form ofskin stimulation used during labor that has a relaxing effect. This study aims to analyze theresult of the Massase Effleurage technique reducing the paint level in first phase favorablemothers on BPM in the environmental area of Panarung Public Health Center at PalangkaRaya. This study uses a Pre-Experimental research method with One Group Pretest Posttest. Design with samples in this study are maternity mothers who are facing the first stage of the latent phase that is included in the inclusion criteria. Bivariate analysis results using the Wilcoxon signed rank test at alpha 0.05 obtained P value 0,000 (p0.05) which there is a significant influence between pain previous massase and after massase, in other words if done Massase Effleurage can reduce pain. So that the results that there an impact the Massase Effleurage technique in pain the first stage of latent phase